A antropotécnica como formação humana em Sloterdijk: da extinção ao exercício - Rauchbach, Pedro Henrique Silveira (2021)
This dissertation aims to analyze a conception of human formation in Sloterdijk's philosophy, based on the anthropotechnic conception proposed by the philosopher. According to the german thinker, man is a kind of domestic animal of himself. This means that he changes through practices and exercises that he performs and that transforms his own being. In other words, man builds himself permanently. For an understanding of this process of reflection, we will use, above all, the books You must change your life (2009) and Rules for the Human Park (1999). Thus Spoke Zarathustra (1883-1885) and On the Genealogy of Morals (1887) are also relevant to our research. The dialogue with Nietzsche is also fundamental for the conception of a man that Peter Sloterdijk proposes to us, we will see how it was from Nietzsche that the thinker of Karlsruhe. These were some of his main theses. Problematically, this starts from the idea of the history of man as a history of exercise. In this way, Sloterdijk launches into the enterprise of trying to understand a little more about the process that made the human constitution possible. With that, it makes a historical retrospective of some of the different practices that constituted the human being as we know it today. From there, we will observe that technique, progress and consumption to a large extent appear as essentially philosophical problems of our time. Along with this, we observe the formation of a bureaucratic and consumerist nature of man, who uses culture only as entertainment, and above all, to fit into some collective. Over this, modern man will always hang in a shadow of extinction. We will see the relationship that exists between this phenomen a with the set of techniques that man produces. Thus, our objective is to try to obtain how Sloterdijk conceived humanity in its entirety, and our central problem as we observe the difficulties that the contemporary world presents to us and what are the perspectives are for overcoming such conditions. We will see that what we practice in our lives is fundamental for our training and even for the constitution of the species, as a great Brazilian composer once expressed "Man is the exercise he does."